Analysis of Numeracy Ability of Elementary School Students at SDN Geluran II Taman: Analisis Kemampuan Berhitung Siswa Sekolah Dasar di SDN Geluran II Taman - Feby Intan Wahana; Feri Tirtoni (Wadah Inovasi Indonesia, 2022)
Research on the Character Analysis of Responsibility of Class IV Students in Face-to-Face Learning During the Covid-19 Pandemic has the aim of knowing the character of the responsibility of grade IV students when carrying out face-to-face learning again and the factors that hinder and support in the character of the responsibility of grade IV students in face-to-face learning during the Covid-19 pandemic. This researcher uses qualitative methods of phenomenology that are descriptive. This research was carried out in January 2022. Data collection techniques in the form of observation, interviews, and documentation. The results of research that has been carried out in the field show that: Character analysis of responsibility of grade IV students during the Covid-19 Pandemic related to the results of (1) The implementation of picket assignments on a regular basis has been fulfilled by most of the grade IV students who have self-awareness with the responsibilities they receive. Such as running a class hygiene picket according to a schedule that has been determined together. (2) Active participation in school activities such as reactivated extra schools, attending tilawah classes on every Thursday. (3) Submit proposals for problem solving that students can do in the classroom such as working on group projects, students are trained to discuss and solve problems that have been provided. the character of responsibility on face-to-face learning in the time of COVID-19 well. Supporting factors there is a school environment that has an adiwiyata school program that can help students in training the character of their responsibilities as well as an active role as well as encouragement from the class teacher, while the inhibiting factor is from within the students themselves and also the friendship environment that can influence